Radon. Advanced regulatory approaches to public radiation protection - S. M. Kiselev; A. M. Marennyy; V. V. Romanov (Радиационная гигиена)
Currently in the Russian Federation the procedure for revision of the national regulatory documents (Radiation Safety Standards (NRB-99/2009) and Basic Sanitary Rules for Ensuring Radiation Safety (OS-PORB 99/2010) has been initiated. In this regard, the authors consider to discuss with the scientific community the necessity to provide amendments in the current Radiation Safety Standards concerning public radiation protection against natural radiation sources, in particular, radon. The main objective is to provide consistence existing national regulatory requirements with the modern international approaches set out in the ICRP and IAEA documents. In this regard, specific proposals on improvement of the regulatory and legislative framework in this field are presented. This will be the basis for the implementation of national radon mitigation strategy in view of the ICRP, WHO and IAEA recommendations and the requirements of the State policy of the Russian Federation in the field of Nuclear and Radiation Safety.